Living Donor Liver Transplantation for Hepatocellular Carcinoma: It Is All about Donors? - Saidi, R. F. (Avicenna Organ Transplantation Institute, 2013)
Background: Live-donor liver transplantation (LDLT) is a valuable option for patients with hepatocellular carcinoma (HCC) as compared with deceased-donor liver transplantation (DDLT); the tumor could be eradicated early. Methods: Herein, we reviewed the outcome of adult patients with HCC who underwent LDLT from 1990 to 2009 in the USA, as reported to United Network for Organ Sharing. Results: Compared to DDLT (n=5858), patients who underwent LDLT for HCC (n=170) were more likely to be female (43.8% vs 23.8%), younger (mean age 48.6 vs 54.9 years) and have more tumors outside Milan criteria (30.7% vs 13.6%). However, the recipients of LDLT for HCC had a significantly shorter mean wait time before transplantation (173 vs 219 days; p=0.04). The overall allograft and patient survival were not different, though more patients in LDLT group were outside Milan criteria. Since implementation of the MELD exception for HCC, DDLT for HCC has increased form 337 (2.3%) cases in 2002 to 1142 (18.7%) in 2009 (p<0.001). However, LDLT for HCC has remained stable from 16 (5.7%) in 2002 to 14 (9.2%) in 2009 (p=0.1). Regions 1, 5 and 9 had the highest rate of LDLT for HCC compared to other regions. Conclusions: LDLT can achieve the same long-term outcomes compared to DDLT in patients with HCC. The current MELD prioritization for HCC reduces the necessity of LDLT for HCC except in areas with severe organ shortage.